Formulation and Test of Burns Healing Effects of Preparations Cream Extract Leaf Nangka Kuning (Vincetoxicum villosum (Blume) Kuntze) - Oktoviani Oktoviani; Camelia Dwi Putri Masrijal; Samwilson Slamet; Nori Wirahmi; Riana Versita; Rose Intan Perma Sari (CV Media Inti Teknologi, 2024)
V. villosum (Blume) Kuntze shows inhibition of the growth of Pseudomonas aeruginosa which is usually the cause of infection in burn wounds. The aim of this research was to formulate V. villosum (Blume) Kuntze leaf extract into a cream preparation and determine the time needed for V. villosum (Blume) Kuntze leaf extract cream to heal burn wounds in rabbits. This research was a type of experimental research. The research was conducted at the University of Bengkulu Laboratory in September 2022-August 2023. The equipment used was the Ohaus Starter 3100 brand pH meter and the NDJ-8S viscometer. The materials used are V. villosum (Blume) Kuntze leaf extract, mice, ethanol solvent. Oil-in-water (O/W) phase cream formulation with 3 variations of stearic acid and triethonolamine emulsifiers (15:4), (16:3) and (17:2). Then the three formulas were evaluated for their preparations which included organoleptic tests, homogeneity tests, pH tests, adhesion tests, spreadability tests, viscosity tests and descriptive stability tests. The activity test against burn wound infections used rabbits consisting of groups K1 (without treatment), K2 (given 0.2% hyaluronic acid cream), P1 (given 2% V. villosum (Blume) Kuntze leaf extract), and P2 (given 2% V. villosum (Blume) Kuntze leaf extract cream). Groups K2, P1 and P2 showed perfect wound healing on day 12. Meanwhile group K1 experienced incomplete wound healing until day 14. Based on the results of the study it can be concluded that the cream formulations I, II and III were declared stable at a temperature of 25º and the extract cream Kuntze V. villosum (Blume) Kuntze leaves showed complete wound healing in 12 days. The results of the Kruskal Wallis test obtained p value = 0.670 > 0.05, which means there is no difference in the length of the healing process for all treatments.